Laboratory investigation on strength of clay composite - Chegenizadeh, Amin; Nikraz, Hamid (The Hong Kong Geotechnical Society and The Hong Kong Polytechnic University, 2011)
Reinforced soil has been among the most effective soil modification materials. Its use has been expanded rapidly into civil engineering, geotechnical engineering and pavement engineering. This study focuses on effect of fiber inclusion on the unconfined compressive strength of composite soil. Plastic fiber was used for this investigation. Fibers were put in composite in random orientation. Fiber contents and aspect ratio have been changed during these tests. The fiber percentage varied from 0 % (for unreinforced samples) to 0.6%. Kaolin Clay was selected as soil. Moreover, effect of fiber inclusion well investigated on cemented clay as well. Unconfined compression tests were carried out to evaluate the behaviour of the composite under different loading condition. The results showed that the unconfined compressive strength of fiber reinforced composite soil was increased by increasing in fiber content and fiber aspect ratio. The fiber aspect ratio and fiber content found to play important rule on the strength of fiber composite clay.